Phosphoproteomics to Characterize Host Response During H3N2 Canine Influenza Virus Infection of Dog Lung - Liu, Yongbo; Fu, Cheng; Ye, Shaotang; Liang, Yingxin; Qi, Zhonghe; Yao, Congwen; Wang, Zhen; Wang, Ji; Cai, Siqi; Tang, Shiyu; Chen, Ying; Li, Shoujun (Frontiers in Veterinary Science, 2020)
Avian-origin H3N2 canine influenza viruses (CIVs) cause severe contagious respiratory disease in dogs, and quickly adapt to new environments. To further understand the mechanism of virus infection and host-virus interactions, we characterized the complete phosphoproteome of dogs infected with H3N2 CIV. Nine-week-old Beagle dogs were inoculated intranasally with 106 EID50 of A/canine/Guangdong/04/2014 (H3N2) virus. Lung sections were harvested at 5 days post-inoculation (dpi) and processed for global and quantitative analysis of differentially expressed phosphoproteins. A total of 1235 differentially expressed phosphorylated proteins were identified in the dog lung after H3N2 CIV infection, and 3,016 modification sites were identified among all differentially expressed proteins. We then performed an enrichment analysis of functional annotations using Kyoto Encyclopedia of Genes and Genomes (KEGG) and gene ontology (GO) database analyses to predict the functions of the identified differential phosphoproteins. Our data indicate that H3N2 CIV infection causes dramatic changes in the host protein phosphorylation of dog lungs. To our knowledge, this is the first study to assess the effect of H3N2 CIV infection on the phosphoproteome of beagles. These data provide novel insights into H3N2-CIV-triggered regulatory phosphorylation circuits and signaling networks and may improve our understanding of the mechanisms underlying CIV pathogenesis in dogs.